Effect of elastic stress and alternating current on corrosion of X80 pipeline steel in simulated soil solution. (June 2019) - Xu, Jin; Bai, Yunlong; Wu, Tangqing; Yan, Maocheng; Yu, Changkun; Sun, Cheng
Abstract: Effects of elastic stress and alternating current (AC) on corrosion behavior of X80 pipeline steel were investigated in a simulated soil solution by electrochemical techniques and surface analysis. Corrosion current density was 40.5 μA/cm 2 by synergistic effects of the stress and the AC current, being about five times of that without the stress and the AC current. Corrosion morphology of the steel coupon was pitting corrosion with application of AC current, and changed from pitting corrosion to moat corrosion under effects of the stress and the AC current. Corrosion of the steel coupon was enhanced by increasing anodic dissolution of iron and porosity of corrosion product film. Highlights: Effect of elastic stress and AC on corrosion of X80 steel was investigated. Elastic stress and AC have synergistic effects on enhancing corrosion of X80 steel. icorr is 40.5 μA/cm 2 by synergistic effects, being about five times of control. Corrosion of steel changes from pitting corrosion to moat corrosion by stress and AC. Corrosion is controlled by increasing anodic dissolution and film degradation.